Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
Zhangir Azerbayev
squashed?
4365a98
raw
history blame
3.65 kB
/-
Copyright (c) 2018 Chris Hughes. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Chris Hughes, Johannes Hölzl, Scott Morrison, Jens Wagemaker
-/
import data.polynomial.derivative
import tactic.linear_combination
import tactic.ring_exp
/-!
# Theory of univariate polynomials
The main def is `binom_expansion`.
-/
noncomputable theory
namespace polynomial
open_locale polynomial
universes u v w x y z
variables {R : Type u} {S : Type v} {T : Type w} {ι : Type x} {k : Type y} {A : Type z}
{a b : R} {m n : ℕ}
section identities
/- @TODO: pow_add_expansion and pow_sub_pow_factor are not specific to polynomials.
These belong somewhere else. But not in group_power because they depend on tactic.ring_exp
Maybe use data.nat.choose to prove it.
-/
/--
`(x + y)^n` can be expressed as `x^n + n*x^(n-1)*y + k * y^2` for some `k` in the ring.
-/
def pow_add_expansion {R : Type*} [comm_semiring R] (x y : R) : ∀ (n : ℕ),
{k // (x + y)^n = x^n + n*x^(n-1)*y + k * y^2}
| 0 := ⟨0, by simp⟩
| 1 := ⟨0, by simp⟩
| (n+2) :=
begin
cases pow_add_expansion (n+1) with z hz,
existsi x*z + (n+1)*x^n+z*y,
calc (x + y) ^ (n + 2) = (x + y) * (x + y) ^ (n + 1) : by ring_exp
... = (x + y) * (x ^ (n + 1) + ↑(n + 1) * x ^ (n + 1 - 1) * y + z * y ^ 2) : by rw hz
... = x ^ (n + 2) + ↑(n + 2) * x ^ (n + 1) * y + (x*z + (n+1)*x^n+z*y) * y ^ 2 :
by { push_cast, ring_exp! }
end
variables [comm_ring R]
private def poly_binom_aux1 (x y : R) (e : ℕ) (a : R) :
{k : R // a * (x + y)^e = a * (x^e + e*x^(e-1)*y + k*y^2)} :=
begin
existsi (pow_add_expansion x y e).val,
congr,
apply (pow_add_expansion _ _ _).property
end
private lemma poly_binom_aux2 (f : R[X]) (x y : R) :
f.eval (x + y) = f.sum (λ e a, a * (x^e + e*x^(e-1)*y + (poly_binom_aux1 x y e a).val*y^2)) :=
begin
unfold eval eval₂, congr' with n z,
apply (poly_binom_aux1 x y _ _).property
end
private lemma poly_binom_aux3 (f : R[X]) (x y : R) : f.eval (x + y) =
f.sum (λ e a, a * x^e) +
f.sum (λ e a, (a * e * x^(e-1)) * y) +
f.sum (λ e a, (a *(poly_binom_aux1 x y e a).val)*y^2) :=
by { rw poly_binom_aux2, simp [left_distrib, sum_add, mul_assoc] }
/--
A polynomial `f` evaluated at `x + y` can be expressed as
the evaluation of `f` at `x`, plus `y` times the (polynomial) derivative of `f` at `x`,
plus some element `k : R` times `y^2`.
-/
def binom_expansion (f : R[X]) (x y : R) :
{k : R // f.eval (x + y) = f.eval x + (f.derivative.eval x) * y + k * y^2} :=
begin
existsi f.sum (λ e a, a *((poly_binom_aux1 x y e a).val)),
rw poly_binom_aux3,
congr,
{ rw [←eval_eq_sum], },
{ rw derivative_eval, exact finset.sum_mul.symm },
{ exact finset.sum_mul.symm }
end
/--
`x^n - y^n` can be expressed as `z * (x - y)` for some `z` in the ring.
-/
def pow_sub_pow_factor (x y : R) : Π (i : ℕ), {z : R // x^i - y^i = z * (x - y)}
| 0 := ⟨0, by simp⟩
| 1 := ⟨1, by simp⟩
| (k+2) :=
begin
cases @pow_sub_pow_factor (k+1) with z hz,
existsi z*x + y^(k+1),
linear_combination x * hz with { normalization_tactic := `[ring_exp] }
end
/--
For any polynomial `f`, `f.eval x - f.eval y` can be expressed as `z * (x - y)`
for some `z` in the ring.
-/
def eval_sub_factor (f : R[X]) (x y : R) :
{z : R // f.eval x - f.eval y = z * (x - y)} :=
begin
refine ⟨f.sum (λ i r, r * (pow_sub_pow_factor x y i).val), _⟩,
delta eval eval₂,
simp only [sum, ← finset.sum_sub_distrib, finset.sum_mul],
dsimp,
congr' with i r,
rw [mul_assoc, ←(pow_sub_pow_factor x y _).prop, mul_sub],
end
end identities
end polynomial